Analisis Kepemimpinan Transformasional pada Perguruan Tinggi Swasta di Kota Sungai Penuh - Herlina, Vivi; Sestriyenti, Enny; Ariani, Fatma (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aimed to analyze the application of transformational leadership in private colleges in Kota Sungai Penuh. This study is a qualitative descriptive analysis based on observations in the field. One of the elements, including leader election is carried out by the foundation. The findings show that there has been a synergy between the foundations and the college. The college leaders in Kota Sungai Penuh has also applied the seven factors of transformational leadership characteristics. However, two elements of transformational leadership were not implemented well: idealized influence and inspirational motivation.